Design, synthesis, and evaluation of a novel macrocyclic anti-EV71 agent. Issue 12 (15th June 2020) - Li, Peng; Wu, Siqi; Xiao, Tianyichen; Li, Yunlong; Su, Zhiming; Wei, Wei; Hao, Fei; Hu, Guoping; Lin, Fusen; Chen, Xinsheng; Gu, Zhengxian; Lin, Tianwei; et al.
Graphical abstract: We describe here the design, synthesis, and evaluation of a macrocyclic peptidomimetic as a potent agent targeting enterovirus A71 (EV71). The compound has a 15-membered macrocyclic ring in a defined conformation. Yamaguchi esterification reaction was used to close the 15-membered macrocycle instead of the typical Ru-catalyzed ring-closing olefin metathesis reaction. The crystallographic characterization of the complex between this compound and its target, 3C protease from EV71, validated the design and paved the way for the generation of a new series of anti-EV71 agents. Abstract: We describe here the design, synthesis, and evaluation of a macrocyclic peptidomimetic as a potent agent targeting enterovirus A71 (EV71). The compound has a 15-membered macrocyclic ring in a defined conformation. Yamaguchi esterification reaction was used to close the 15-membered macrocycle instead of the typical Ru-catalyzed ring-closing olefin metathesis reaction. The crystallographic characterization of the complex between this compound and its target, 3C protease from EV71, validated the design and paved the way for the generation of a new series of anti-EV71 agents.